2011
DOI: 10.1080/10550887.2011.554777
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Trial of Two Behavioral Interventions to Improve Outcomes Following Inpatient Detoxification for Alcohol Dependence

Abstract: To determine if the addition of a behavioral intervention during alcohol detoxification would facilitate initiation of subsequent care, we randomized 150 detoxification patients to receive: treatment as usual (TAU), a Motivation Enhancement Therapy (MET) intervention, or a Peer-delivered Twelve Step Facilitation (P-TSF) intervention. The main outcome was the initiation of any type of subsequent care (i.e., professional treatment or self-help) within 30 and 90 days of discharge. Other outcomes included: alcohol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
22
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 29 publications
3
22
2
Order By: Relevance
“…Relapse curves usually tend to be exponential and steeper in the early phase after detoxification (Blondell et al, 2011;Paparrigopoulos et al, 2011). However, for 90% of subjects in the present study, a typical drinking day was a heavy drinking day, and 70% reported 4 or more drinking day per week, before detoxification.…”
Section: Discussioncontrasting
confidence: 49%
“…Relapse curves usually tend to be exponential and steeper in the early phase after detoxification (Blondell et al, 2011;Paparrigopoulos et al, 2011). However, for 90% of subjects in the present study, a typical drinking day was a heavy drinking day, and 70% reported 4 or more drinking day per week, before detoxification.…”
Section: Discussioncontrasting
confidence: 49%
“…Overall however, results of factor analysis, coupled with the high internal reliability for the total score, support the notion of one overall construct of adverse consequences, consistent with prior interpretations of the SIP (Allensworth-Davies, Cheng, Smith, Samet, & Saitz, 2012; Alterman et al, 2009; Bender et al, 2007; Blanchard et al, 2003a). These findings support the use of the SIP total score when reporting results, as is most common in the literature (e.g., Blondell, et al, 2011; Brower, Krentzman, & Robinson, 2011; Clark, et al, 2012), with limited use of the three-item subscale scores.…”
Section: Discussionsupporting
confidence: 78%
“…Given prior literature indicating that many inpatients with AUDs forgo follow‐up treatment (Blondell et al., ; Saitz et al., ), we were surprised that the vast majority of veterans in both study groups saw an addiction treatment specialist in the last 14 days after hospital discharge. In light of these findings, and because inpatients in need of alcohol detoxification are likely to have extensive treatment needs, our findings indicate that the most optimal measure of follow‐up care would be a measure based on continued engagement in substance‐use disorder treatment, rather than the initiation of any treatment.…”
Section: Discussionmentioning
confidence: 90%